Micropropagación en tacaco (Sechium tacaco); presentación de resultados - Monge Pérez, José Eladio (2019)
Investigadores: Zerpa Catanho, Dessireé, Viñas, María, Jiménez García, Víctor, Hernández Pridybailo, Andrés y Murillo Quesada, Marcelo Efrén